The Regional Earth System Model RegCM‐ES: Evaluation of the Mediterranean Climate and Marine Biogeochemistry. (24th September 2020) - Reale, Marco; Giorgi, Filippo; Solidoro, Cosimo; Di Biagio, Valeria; Di Sante, Fabio; Mariotti, Laura; Farneti, Riccardo; Sannino, Gianmaria
Abstract: We introduce a new version of the Earth System Regional Climate model RegCM‐ES and evaluate its performances for the first time over the Mediterranean region. The novel aspect of this coupled system is the possibility to simulate the dynamics of the marine ecosystem through a biogeochemical model, BFM (Biogeochemical Flux Model), coupled online with the ocean circulation model MITgcm (MIT general circulation model). The validation of atmosphere and ocean components has shown that the model is able to capture interannual and intermonthly variabilities of the atmospheric heat fluxes and spatial patterns of land surface temperature, precipitation, evaporation, and sea surface temperature with a general improvement compared to previous versions. At the same time, we diagnosed some prominent deficiencies as a warm and dry bias associated in summer with the resolution of the atmospheric module and the tuning of the boundary layer and convective precipitation scheme. On the biogeochemical side, RegCM‐ES shows good skills in reproducing mean values and spatial patterns of net primary production, phosphate, and horizontal/vertical patterns of chlorophyll‐a. Limitations in this case include deficiencies mainly in the simulation of mean values of nitrate and dissolved oxygen in the basin which have been associated with too large vertical mixing throughout the water column, deficiencies in the boundary conditions, and solubility computations. Overall, RegCM‐ES has the potential to become a suitable tool for the analysis of the impacts of climate change on the ocean and marine biogeochemistry in the Mediterranean region and many other domains. Plain Language Summary: We evaluate the skills of a new version of a regional coupled model in reproducing climate and marine biogeochemistry of the Mediterranean region. We find that the model, despite some persistent biases, is able to capture most key aspects of the regional Mediterranean climate and its marine biogeochemistry. Key Points: A new version of the Earth System Regional Climate Model RegCM‐ES is described and validated in the Mediterranean region The new development of this modeling tool is the possibility to simulate the dynamics of marine ecosystems The model shows good skills in reproducing net primary production, chlorophyll‐a, and phosphate in the basin